Mammography Among Women Residing in Urban Versus Rural Utah: Breast Cancer Survival - Quinn Tanner; Chun‐Pin Chang; Karen Curtin; James VanDerslice; Lisa Gren; Vikrant Deshmukh; Michael Newman; Ankita Date; Mark Dodson; N. Lynn Henry; Mia Hashibe (Cancer Medicine)
ABSTRACT Background Annual or biennial breast cancer screenings are recommended for women 40 and older. Women residing in rural areas have worse breast cancer survival rates than urban women, but no study has focused on rural versus urban residence in Utah regarding breast cancer screening and mortality. Methods Cases (n = 14,516) were women aged > 39 diagnosed with a first primary invasive breast cancer between 1998 and 2017 in Utah. Controls (n = 63,117) without a history of breast cancer were matched to cases by birth year and birth state. Mammography screening status was identified by Current Procedural Terminology (CPT) codes. Logistic regression was used to assess the odds of breast cancer diagnosis. The Cox proportional hazards model was used to assess survival outcomes for rural and urban breast cancer patients based on screening status. Results Screening mammography usage among rural patients diagnosed with breast cancer was lower (17.7%) than urban usage (20.7%). Usage of screening mammograms resulted in higher odds of breast cancer diagnosis at localized stage rather than at a regional and distant stage. Rural breast cancer cases had a higher proportion of deaths, and a lower proportion screened, than urban breast cancer cases. Hazard ratios showed that screening mammography usage was associated with better survival among both rural (HR = 0.50, 95% CI = 0.44–0.57) and urban (HR = 0.56, 95% CI = 0.39–0.82) breast cancer cases. Conclusion Screening mammography usage was associated with better overall survival regardless of place of residence. Removing barriers and improving information regarding breast cancer screenings are needed in both rural and urban settings in Utah to increase mammography usage, with the overall goal of increasing early detection and outcomes of breast cancer.